Cervical cancer patients’ knowledge and experiences with palliative care – A qualitative study - Jaclyn A. Wall; Tamara Nix-Parker; Katherine Klein; Marie A. Bakitas (Gynecologic Oncology Reports)
Objective: There is limited research examining palliative care (PC) knowledge and experiences in patients with cervical cancer. As this may inform who may benefit from specialty PC services, we investigated PC awareness, perspectives, needs, and acceptability in this population. Methods: We conducted a qualitative study of patients with newly diagnosed (<12 months) cervical cancer. Eligible patients were > 18 years old and English-speaking. Semi-structured interview topics included knowledge/perceptions of PC, knowledge/perceptions of hospice, and experiences with PC or hospice. Participants were then read a brief definition and overview of services provided by PC (education). We then explored perceptions of PC acceptability and timing. Interviews were deidentified, professionally transcribed, and coded. Codes were grouped into categories and themes. Results: Seventeen patients participated. Median age was 52, 64 % were white, all had insurance. 35 % had stage I disease, 17.6 % stage II, and 47 % stage III. Most had minimal PC knowledge (12/17, 70.6 %) but were aware of hospice (16/17, 94.1 %) and understood it as end-of-life care (10/17, 58.8 %). Following our education, most felt PC would be beneficial (13/17, 76.5 %), and favored early introduction in their care (11/17, 64.7 %). We identified four main themes: two pre-education (PC knowledge is lacking, hospice is well-understood and favorably viewed) and two post-education (PC would provide an unmet benefit, early PC is preferable). Conclusions: PC knowledge was limited. However, following brief education, most patients found it desirable and favored early integration. This highlights the need for further research on developing early PC initiatives for patients with cervical cancer.